Sleep disturbance and cognitive functioning among firefighters. (October 2021) - Stout, Jeremy W; Beidel, Deborah C; Brush, David; Bowers, Clint
Firefighters are at risk for chronic sleep disruption due to their rotating 24-hour on and 48-hour off work schedule and hazardous work conditions. Forty-five firefighters were assessed to determine the impact of their shift schedule on sleep duration, sleep quality, processing speed, sustained attention, vigilance, and mental health. Assessments were conducted at the start and end of shift. Firefighters endorsed sleeping 5 hours 21 minutes at work, and the results suggest that even minimal sleep disruption affected cognitive functioning (e.g. processing speed, visual-motor coordination, and reaction time), increasing the likelihood of poor work performance or injury.